Features of Social and Economic Support of the Territorial Subjects of the Russian Federation - Klyuchnikov, Denis A.; Shichiyakh, Rustem A.; Kolpak, Eugeny P.; Tupchienko, Vitaly A.; Volodin, Viktor M.; Isaev, Albert K. (International Journal of Economics and Financial Issues, 2016)
The political, social and economic reforms of the 90-ies of the last century, along with the activation of such social phenomena as alcoholism, drug addiction, depopulation, etc., gave rise to some processes fundamentally new for Russia - poverty, unemployment, child neglect, forced migration characterized by steady growth of population in need of social support. All these phenomena have identified urgent need to develop a system of measures on social support of the population of Russia, mitigation of negative social consequences of economic reforms. However, the relaxation role the state’s role, formation of market mechanisms in the absence of the effective system of social process management in the situation of economic slack, realistic lack of consistency of social policy measures not only failed to alleviate the existing social risks, but often contributed to their increase. The most significant social problems today, despite some improvement in the standard of living of the past few years, are increasing polarization of incomes, the natural decline in population and its marginalization. The social support system existing in contemporary Russia largely corresponds to the socialist mode of management; it is not adapted to the current social and economic factors and conditions of development of Russia. Keywords: economical good, social and economic support, country population JEL Classifications: H50, H53, L81, L84, M31